Poetry, Painting, Patchwork: Peter Handke's Intermedial Writing of Die Lehre der Sainte‐Victoire. (26th April 2019) - Haubenreich, Jacob
Abstract : A turning point in Peter Handke's career following a deep crisis of writing, the text Die Lehre der Sainte‐Victoire (1980 ) represents a fundamental transformation of the writer's poetological project and material practice of writing. The poetry of Friedrich Hölderlin, the paintings of Paul Cézanne, and the patchwork method of clothing designer Domenika Kaesdorf emerge as key influences within this transformation. Hölderlin's idealization of the poet's task and Cézanne's and Kaesdorf's physical methods, however, are no mere metaphors for Handke's process of writing; rather, Handke takes up and translates these modes into his material practice. This essay thus models a particular kind of reception history, one in which textual thematics are actualized in physical practice and semantic content is entangled in the material and visual dimensions of texts. Such an approach exemplifies the potential of incorporating materiality and meaning to expand the field of textual interpretation.